2018
DOI: 10.1002/jcp.27744
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA ZNF609 functions as a competitive endogenous RNA to regulate FOXP4 expression by sponging miR‐138‐5p in renal carcinoma

Abstract: Circular RNA (circRNA) play important roles in the pathological processes of many diseases. By analyzing the results of the GSE100186 chip, we found that the expression of circRNA ZNF609 (circ‐ZNF609) was significantly increased in renal cell carcinoma. Recently, there are studies showing that circ‐ZNF609 can regulate cell proliferation and invasion ability of various cells. In this study, we investigated whether circ‐ZNF609 may affect cell invasion and proliferation in renal carcinoma. Quantitative reverse tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 30 publications
4
84
0
Order By: Relevance
“…Recent studies have demonstrated that circRNA played efficacy in RC by mediating other factors. A study reflected circZNF609 exerted promoting carcinoma efficacies by modulating miR‐138‐5p in RC (Xiong, Zhang, & Song, ), other research reflected circciRs‐126 can be a landmark in kidney damage (Kolling et al, ). Furthermore, circFNDC3B exerted anticarcinoma efficacies by modulating miR‐1178‐3p in bladder carcinoma (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that circRNA played efficacy in RC by mediating other factors. A study reflected circZNF609 exerted promoting carcinoma efficacies by modulating miR‐138‐5p in RC (Xiong, Zhang, & Song, ), other research reflected circciRs‐126 can be a landmark in kidney damage (Kolling et al, ). Furthermore, circFNDC3B exerted anticarcinoma efficacies by modulating miR‐1178‐3p in bladder carcinoma (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a word, these results validated that suppression of circ-TFF1 hindered breast cancer cell growth in vivo. 26 However, the investigation of circRNAs in cancers was still inadequate.…”
Section: Knockdown Of Circ-tff1 Impeded Cell Growth Of Breast Cancementioning
confidence: 99%
“…For instance, circ-HIAT1 acted as a metastatic inhibitor to prevent androgen receptor (AR)-accelerated RCC cell migration and invasion by de-regulating miR-195-5p [7]. circ-ZNF609 was significantly overproduced in RCC cell lines, and thus promoted the cell proliferation and invasion through a novel network that was comprised by circ-ZNF609 and miR-138-5p [17]. What's important, Zhang et al demonstrated that circNRIP1 promoted tumor metastasis in vivo by inducing proliferation and migration as well as the activation of AKT/mTOR cascade in GC [8].…”
Section: Discussionmentioning
confidence: 99%